Floristic Composition and Diversity in Plots of Early Post-Agricultural Succession in Four Agroecosystems in the District of Cajatambo, Lima - Castro-Cepero, V. (2019)
In this paper, the floristic composition is studied in plots of early post-agricultural succession induced in four agroecosystems (Ocopata, Rancas, Tupicocha and Ucupi) in the district of Cajatambo, Lima. The plots are located between 2,992 masl and 4,220 masl in three plant formations (agriculture, scrubland and grassland), and the description of the floristic composition was made before and after inducing the succession between 2015 and 2017. The number of determined plants is 78, all of which belong to 30 botanical families, of which the Asteraceae (16 species), Fabaceae (11 species) and Poaceae (8 species) families stand out. Indeed, the only common species among the four agroecosystems is Medicago polymorpha; moreover, five species appear in three of the four agroecosystems: Brassica rapa subsp. campestris and Verbena litoralis (Ocopata, Tupicocha and Rancas), Oenothera rosea and Trifolium repens (Ocopata, Rancas and Ucupi) and Bidens andicola (Tupicocha, Rancas and Ucupi).